L'enseignement des sciences à l'université : traditions ou innovations ? - Reine El Khoury; Saouma BouJaoude; Daniel Favre; Fadi El Hage
This research aims to probe teaching practices of science faculty members from four science faculties in Lebanon. A questionnaire survey was conducted among twenty-four science faculty members, and classroom observations followed by semi-structured interviews were conducted with nine science faculty members to identify traditional teaching methods, innovative practices and mixed teaching methods, as well as teaching constraints preventing the use of innovative practices.